La influencia de la programación televisiva nacional en la franja horaria de 15h00 a 18h00 en las relaciones interpersonales de los niños de la escuela Cristóbal Colón del cantón Salcedo en el período Abril-Agosto del 2014 - Ortega Mera, Mayra Alejandra (2015)
The media throughout the History has had a great influence on human beings‟ life. It has become an information, education, and entertainment means. This study was carried out with children of „Cristobal Colón‟ Elementary School, located in Salcedo Town. In addition, the implementation of workshops were developed as a guide for parents about the impact that media has in their children‟s lives. The Proposal was developed taking into account relevant literature reviews and research methods such as observation, survey, and interview. Children in the school and their Parents were surveyed and the specialist in children psychology was interviewed. Finally, it was concluded that the development of workshops are necessary for parents and children in order to improve their perspective and differentiate media messages.